Inventarisasi Ekosistem Mangrove di Pesisir Randutatah, Kecamatan Paiton, Jawa Timur - Syamsuddin, Nurmujahidah; Santoso, Nyoto; Diatin, Iis (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2019)
Mangrove ecosystem is a region that acts as a transition between land and sea. This ecosystem has ecological, socio-economic and physical functions. The decline in the quality and quantity of mangrove forests has resulted in very alarming impacts, such as increased abrasion, reduced fishing catches, seawater intrusion, and others. This study aims to analyze the biodiversity of mangrove ecosystem in the Randutatah coal. The results showed that mangrove ecosystems were dominated by Rhizophora stylosa species with the highest INP values in tillers and tree categories. Observations of fauna in the area found 2 types of mammals, 34 species of birds, 7 species of herpetofauna, and 9 species of insects. the wealth of bird species in this region is high. Phytoplankton composition is dominated by Bacillariophyceae class, zooplankton is dominated by crustacean class, and nekton is dominated by Mugilidae class. Mangrove conditions in Randutatah can increase biodiversity in these locations, as well as the condition of the waters around the mangrove ecosystem that become fertile so that it can be used by the community to catch fish or crabs that have an impact on the growth of the economic value of the community.